Lead exposure is a risk for worsening bone mineral density in middle-aged male workers. (September 2014) - Akbal, Ayla; Tutkun, Engin; Yılmaz, Hınç
Abstract Objective: Lead exposure linked to osteoporosis in women. However, there is no direct evidence whether lead exposure has effects on bone metabolism in middle-aged male subjects. Therefore, the present study investigated the relationship between bone mineral densitometry measurements, bone markers, endocrine hormones and blood lead levels. Material and methods: The present study included lead exposure patients (n: 30) and control subjects (n: 32). We recorded information on patient demographics and risk factors of osteoporosis. Blood lead levels were evaluated using Varian AA 240Z atomic absorption spectrophotometry. Bone mineral density measurements were measured using dual-energy X-ray absorptiometry. Results: Each lumbar T and Z scores in the lead exposure group were lower than the control group. There were no significant differences in femur neck and femur total T and Z scores between two groups. Blood lead levels were also negatively correlated with lumbar 2-4 T score, total lumbar T score, lumbar 2-4 Z score and total lumbar Z score. Urinary hydroxyproline and urinary deoxypyridinoline levels in the lead exposure group were significantly higher compared to controls. Blood lead levels were strong, positively correlated with urinary deoxypyridinoline. Endocrine hormone levels and 1, 25-dihydroxy-vitamin D3 levels were comparable between lead exposure and control group. Conclusion: Lead exposure in male workers is an important factor for deterioration in bone mineral density. We should be screening blood lead levels and history of lead exposure in male osteoporosis.